2007
DOI: 10.2298/vsp0706399p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tadalafil on erectile dysfunction in male patients with diabetes mellitus

Abstract: Tadalafil is an effective tool for treating ED in diabetes patients. In some situations tadalafil application could replace prostaglandin test. The sexual sphere motivation leads to the improvement of glucoregulation in DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The proportion of subjects with IIEF‐EF domain scores ≥26 was 23.3% (2.5 mg) and 22.1% (5 mg) [24]. On demand treatment of tadalafil in diabetic male patients improved ED by 58% and 60% towards SEP2 and SEP3, respectively [25]. Another study by Goldstein et al., who investigated tadalafil 20 mg administrated as needed prior to sexual activities in men with ED and multiple comorbidities including diabetes, for 12 weeks, demonstrated a significant mean change of 7.6 from baseline in EF domain score.…”
Section: Discussionmentioning
confidence: 98%
“…The proportion of subjects with IIEF‐EF domain scores ≥26 was 23.3% (2.5 mg) and 22.1% (5 mg) [24]. On demand treatment of tadalafil in diabetic male patients improved ED by 58% and 60% towards SEP2 and SEP3, respectively [25]. Another study by Goldstein et al., who investigated tadalafil 20 mg administrated as needed prior to sexual activities in men with ED and multiple comorbidities including diabetes, for 12 weeks, demonstrated a significant mean change of 7.6 from baseline in EF domain score.…”
Section: Discussionmentioning
confidence: 98%
“… 26 In addition, Popovic et al reported that combination of antidiabetic drugs and tadalafil can even improve the bioavailability and efficacy of tadalafil. 27 Repaglinide ( Fig. 1b ), a BCS class II drug with poor aqueous solubility, is an oral antidiabetic drug for clinical treatment of type II diabetes mellitus by stimulating insulin release from pancreatic β-cells.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of subjects with IIEF-EF domain scores ≥ 26 (normal erectile function) was 23.3% (2.5 mg) and 22.1% (5 mg) [10]. On-demand treatment with tadalafil in patients with DM improved ED by 58% and 60% for SEP2 and SEP3, respectively [11]. The Scheduled Use vs. On-demand Regimen Evaluation study in 14 European countries showed that >40% of patients with DM and ED had a normal IIEF-EF domain score (≥26), and the proportion of "yes" responses was 73% for SEP2 and ≥58% for SEP3 after on-demand or three-times-per-week administration of 20 mg tadalafil [12].…”
Section: Discussionmentioning
confidence: 99%